"On the Fence" versus "All in": Insights from Turtles for the Evolution of Aquatic Locomotor Specializations and Habitat Transitions in Tetrapod Vertebrates. (23rd October 2016) - Blob, Richard W.; Mayerl, Christopher J.; Rivera, Angela R. V.; Rivera, Gabriel; Young, Vanessa K. H.
Abstract : Though ultimately descended from terrestrial amniotes, turtles have deep roots as an aquatic lineage and are quite diverse in the extent of their aquatic specializations. Many taxa can be viewed as "on the fence" between aquatic and terrestrial realms, whereas others have independently hyperspecialized and moved "all in" to aquatic habitats. Such differences in specialization are reflected strongly in the locomotor system. We have conducted several studies to evaluate the performance consequences of such variation in design, as well as the mechanisms through which specialization for aquatic locomotion is facilitated in turtles. One path to aquatic hyperspecialization has involved the evolutionary transformation of the forelimbs from rowing, tubular limbs with distal paddles into flapping, flattened flippers, as in sea turtles. Prior to the advent of any hydrodynamic advantages, the evolution of such flippers may have been enabled by a reduction in twisting loads on proximal limb bones that accompanied swimming in rowing ancestors, facilitating a shift from tubular to flattened limbs. Moreover, the control of flapping movements appears related primarily to shifts in the activity of a single forelimb muscle, the deltoid. Despite some performance advantages, flapping may entail a locomotor cost in terms of decreased locomotor stability. However, other morphological specializations among rowing species may enhance swimming stability. For example, among highly aquatic pleurodiran turtles, fusion of the pelvis to the shell appears to dramatically reduce motions of the pelvis compared to freshwater cryptodiran species. This could contribute to advantageous increases in aquatic stability among predominantly aquatic pleurodires. Thus, even within the potential constraints of a body plan in which the body is encased by a shell, turtles exhibit diverse locomotor capacities that have enabled diversification into a wide range of aquatic habitats.